1990
DOI: 10.1136/bmj.300.6736.1383
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviours for HIV infection among drug users in prison.

Abstract: Objective-To study a group of injecting drug users to establish the degree of iilicit drug Results -The average time spent in custody before the study was 20-6 months (range 1-72). Most prosecutions were directly or indirectly related to drug taking. 47 Ofthe 50 respondents reported taking at least one illicit drug while in custody; 33 by injection, 26 of whom had shared injecting equipment. 30 Had been treated for drug dependency by the prescribing of drugs while in prison. While in custody, one woman and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 2 publications
5
28
2
Order By: Relevance
“…A recent Scottish study found that the incidence of HCV ranged from 1 per 100 personyears in prison among non-intravenous-drug-using inmates to 27 per 100 person-years of imprisonment among those who shared needles while in prison [Champion et al, 2003]. These data suggest that the transmission of infections in prison does occur, although the rates of transmission can be considered as relatively low, which is consistent with the findings that the frequency with which inmates engage in risk behavior increases when they are not actually in prison [Carvell and Hart, 1990].…”
Section: Discussionsupporting
confidence: 85%
“…A recent Scottish study found that the incidence of HCV ranged from 1 per 100 personyears in prison among non-intravenous-drug-using inmates to 27 per 100 person-years of imprisonment among those who shared needles while in prison [Champion et al, 2003]. These data suggest that the transmission of infections in prison does occur, although the rates of transmission can be considered as relatively low, which is consistent with the findings that the frequency with which inmates engage in risk behavior increases when they are not actually in prison [Carvell and Hart, 1990].…”
Section: Discussionsupporting
confidence: 85%
“…They reported less frequent injecting in prison than outside prison, but higher lev-els of sharing injecting equipment among larger cohorts of individuals. This latter finding is in keeping with other studies Bird, Gore, Cameron, Ross, & Goldberg, 1995;Bird, Gore, Jolliffe, & Burns, 1992;Carvell & Hart, 1990;Dolan, Hall, & Wodak, 1996;Gore et al, 1995;Gore, Bird, Burns, Ross, & Goldberg, 1997;Long et al, 2001;Malliori et al, 1998;Turnbull, Dolan, & Stimson, 1991). Turnbull et al also reported that needles and syringes were rarely if ever disposed of in prison but were passed on to other inmates on release (Turnbull et al, 1994).…”
Section: Introductionsupporting
confidence: 82%
“…It is clear that these practices (starting to inject, sharing injecting equipment frequently with a larger cohort of individuals and inadequate cleaning and sterilising of injecting equipment) increase the likelihood of contracting HIV, hepatitis B and, in particular, hepatitis C in prison. The validity of the study findings are indicated by the similarity of the findings to those from other studies (Bird et al, 1992Carvell & Hart, 1990;Dillon, 2001;Dolan et al, 1996;Gore et al, 1995Gore et al, , 1997Malliori et al, 1998;Turnbull et al, 1991Turnbull et al, , 1994.…”
Section: Discussionsupporting
confidence: 60%
“…Although we lacked statistical power to undertake a multivariable meta-regression, univariable analyses suggested that study-level characteristics -recruitment setting, recruitment method, baseline HCV prevalence of the study sample, and mean/median time since onset of injecting of the study samplewere potential modifiers of the pooled association between N/S sharing and HCV prevalence/incidence. Studies that recruited participants in prison generally showed larger effect sizes compared with studies that recruited participants in drug treatment settings, which may reflect that individuals who are incarcerated tend to engage in riskier behaviour, both inside and outside prison (Carvell & Hart, 1990;Jurgens, Ball, & Verster, 2009). By contrast, studies that recruited at drug treatment sites generally had lower ORs of the association between N/S sharing and HCV.…”
Section: Discussionmentioning
confidence: 91%